1994
DOI: 10.1177/0310057x9402200508
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Induction Agents in Paediatric Anaesthesia—Cardiovascular Effects and Recovery

Abstract: We studied 30 children undergoing circumcision randomly allocated to receive either thiopentone 4 mg.kg-I , propofol2.5 mg.kg-I or midazolam 0.5 mg.kg-I (n=JO) IV over 30 seconds at induction of anaesthesia. Blood pressure and pulse rate during the first 15 minutes of induction were recorded by a Finapres 2300e and a Cardiocap CM-J04, and changes from preinduction baseline compared between the three induction agents and the two recording instruments. Postoperatively, blood levels of the induction agents were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
7
19
0
Order By: Relevance
“…The present study extends the latter results by showing that buccal premedication with 0.2 mg.kg )1 midazolam is associated with significant further slowing of reaction time and impairment of fine motor control at the time of discharge. The results are broadly consistent with those of Jones et al [9] in their study of induction with 0.5 mg.kg )1 midazolam, propofol or thiopental, and maintenance with nitrous oxide and halothane in children aged 4-12 years, all of whom received intravenous Table 2 The number of children correctly recalling and recognising pictoral stimuli postoperatively prior to discharge (recall only), and 48 h later at home, as a function of premedication with midazolam or placebo. Children having placebo correctly recalled significantly more postoperatively (p = 0.014) and at 48 h (p = 0.012), and correctly recognised more stimuli at 48 h (p < 0.001), than those having midazolam.…”
Section: Discussionsupporting
confidence: 92%
“…The present study extends the latter results by showing that buccal premedication with 0.2 mg.kg )1 midazolam is associated with significant further slowing of reaction time and impairment of fine motor control at the time of discharge. The results are broadly consistent with those of Jones et al [9] in their study of induction with 0.5 mg.kg )1 midazolam, propofol or thiopental, and maintenance with nitrous oxide and halothane in children aged 4-12 years, all of whom received intravenous Table 2 The number of children correctly recalling and recognising pictoral stimuli postoperatively prior to discharge (recall only), and 48 h later at home, as a function of premedication with midazolam or placebo. Children having placebo correctly recalled significantly more postoperatively (p = 0.014) and at 48 h (p = 0.012), and correctly recognised more stimuli at 48 h (p < 0.001), than those having midazolam.…”
Section: Discussionsupporting
confidence: 92%
“…In the adapted scheme, the dosage in the youngest age group is relatively the highest and is lower for older age groups. This was based on the model of partition of propofol, which is a 3‐compartment model (3– 6,11– 16).…”
Section: Discussionmentioning
confidence: 99%
“…We found that relatively more propofol was needed, especially in the youngest age groups, to fill the central compartments, but with a longer duration the dosage had to be reduced relative to older patients because of slower metabolism of the drug and other properties of the compartments in children of these age groups (11– 13,16– 18,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations